X‐Ray‐Controlled Generation of Peroxynitrite Based on Nanosized LiLuF4:Ce3+ Scintillators and their Applications for Radiosensitization. Issue 43 (10th September 2018) - Du, Zhen; Zhang, Xiao; Guo, Zhao; Xie, Jiani; Dong, Xinghua; Zhu, Shuang; Du, Jiangfeng; Gu, Zhanjun; Zhao, Yuliang
Abstract: Peroxynitrite (ONOO − ), the reaction product derived from nitric oxide (NO) and superoxide (O2 − ), is a potent oxidizing and nitrating agent that modulates complex biological processes and promotes cell death. Therefore, it can be expected that the overproduction of ONOO − in tumors can be an efficient approach in cancer therapy. Herein, a multifunctional X‐ray‐controlled ONOO − generation platform based on scintillating nanoparticles (SCNPs) and UV‐responsive NO donors Roussin's black salt is reported, and consequently the mechanism of their application in enhanced therapeutic efficacy of radiotherapy is illustrated. Attributed to the radioluminescence and high X‐ray‐absorbing property of SCNPs, the nanocomposite can produce NO and O2 − simultaneously when excited by X‐ray irradiation. Such simultaneous release of NO and O2 − ensures the efficient X‐ray‐controlled generation of ONOO − in tumors. Meanwhile, the application of X‐rays as the excitation source can achieve better penetration depth and induce radiotherapy in this nanotherapeutic platform. It is found that the X‐ray‐controlled ONOO − ‐generation platform can efficiently improve the radiotherapy efficiency via directly damaging DNA, downregulating the expression of the DNA‐repair enzyme, and overcoming the hypoxia‐associated resistance in radiotherapy. Therefore, this SCNP‐based platform may provide a new combinatorial strategy of ONOO − and radiotherapy to improve cancer treatment. Abstract : A nanocomposite containing scintillating nanoparticles and Roussin's black salt is developed for X‐ray‐induced ONOO − generation and applications in radiosensitization. Afterward, they are explored as poly(ADP‐ribose) poerase inhibitors and hypoxic radiosensitizers to inhibit the repair of the damaged DNA and overcome hypoxia‐associated radioresistance.